The Potential of Lime Peel Extract Mouthwash as A Non-Pharmacological Preparation Inhibits Caries Bacteria - Elsa L; Supriyana Supriyana; Lanny Sunarjo (Syntax Corporation Indonesia, 2023)
Dental caries is a disease of the hard tissue of the teeth that attacks the enamel, dentin and cementum which is characterized by the demineralization of the hard tissue of the teeth. Streptococcus mutans bacteria itself is one of the bacteria found and lives in the oral cavity. One of the infectious diseases caused by the process of removing minerals due to bacteria on the surface of the teeth is called caries. An alternative choice as an effort to solve the problem of inhibiting caries-causing bacteria is by using herbal mouthwash. One of them is lime peel. Lime peel has the potential to inhibit Streptococcus mutans bacteria as indicated by the formation of an inhibition zone, which is formed against Streptococcus mutans bacteria. Making a mouthwash preparation of lime peel extract (Citrus Aurantifolia) which is feasible and effective in inhibiting the growth of Streptococcus mutans bacteria. This research is a true experiment with post test only control group design. This design was chosen because it was grouped into treatment and control groups. The intervention was given in the form of lime peel extract mouthwash with concentrations of 15%, 25% and 50%, while the administration of the UNISSULA Faculty of Medicine Biomedical Laboratory Mouthwash Formula was the control group. Based on the average inhibition graph within 24 hours, the concentration of extract mouthwash The lowest lime peel was 15% = 8.83 mm, the highest inhibition zone was at a concentration of 50% = 10.50 mm, 25% concentration = 9.80 mm, the control group Formula Mouthwash Biomedical Laboratory Concoction of the Faculty of Medicine UNISSULA = 10, 13mm. Lime peel extract mouthwash is feasible and effective in inhibiting streptococcus mutans which causes caries.